2008
DOI: 10.1166/jnn.2008.241
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence of Silica Nanostructures from Bioreactor Culture of Marine Diatom Nitzschia frustulum

Abstract: The marine diatom Nitzschia frustulum is a single-celled photosynthetic organism that uses soluble silicon as the substrate to fabricate intricately patterned silica shells called frustules consisting of 200 nm diameter pores in a rectangular array. Controlled photobioreactor cultivation of the N. frustulum cell suspension to silicon starvation induced changes in the nanostructure of the diatom frustule, which in turn imparted blue photoluminescence (PL) to the frustule biosilica. The photoluminescent properti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(63 citation statements)
references
References 0 publications
3
59
1
Order By: Relevance
“…Previous work in our laboratory has shown that diatom biosilica possesses intrinsic PL that is dependent upon the development of nanoscale features on the frustule surface during the diatom cell cultivation. [21][22][23] The studies of De Stefano and coworkers have shown that the adsorption of electrophilic and nucleophilic gas molecules onto diatom biosilica changed the PL spectra. [24][25][26][27] In general, PL emission is generated when electron-hole pairs created by absorbing incident photons from the excitation source radiatively recombine and discharge photons of lower energy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous work in our laboratory has shown that diatom biosilica possesses intrinsic PL that is dependent upon the development of nanoscale features on the frustule surface during the diatom cell cultivation. [21][22][23] The studies of De Stefano and coworkers have shown that the adsorption of electrophilic and nucleophilic gas molecules onto diatom biosilica changed the PL spectra. [24][25][26][27] In general, PL emission is generated when electron-hole pairs created by absorbing incident photons from the excitation source radiatively recombine and discharge photons of lower energy.…”
Section: Discussionmentioning
confidence: 99%
“…The fraction of light emitted from the sample surface at a 458 angle was sent through a 360-nm UV cut-off filter to remove the reflected laser excitation signal, focused to a 1.0-mm beam width, and then measured with an Acton Inspectrum 300 spectrometer equipped with a CCD detector (0.20-mm slit width, 300 gratings per millimeter, 2 000 ms integration time). Functionalized diatom biosilica from the immunocomplex specificity experiments was centrifuged (10 min, 325Âg), and 1.0 mg of wet pellet was loaded into a PL sample holder described elsewhere [22]. These samples were excited with a 337-nm light source from a 175 W Xenon lamp (Spectral Products, #ASB-XE-175EX) equipped with a Spectral Products CM100-1/8 monochromator (1 200 grooves per millimeter, 0.60-mm slit width) with a 400-nm cut-off filter.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The intense bands located at 470, 810 and 1090 cm -1 are due to the bending vibration, and the symmetric and asymmetric stretching vibration of Si-O-Si network of the biosilica [23], while the shoulder in the 1100-1200 cm -1 region is related to the out-of-phase Si-O stretching vibrations [25]. Another similarities are the broad band observed around 3435 cm -1 and the weak band located at 1640 cm -1 , they are ascribed to the O-H stretching and bending vibration of hydroxyl groups of surface-bound water and water adsorbed in the porous structures [19,24], which also includes the H-O-Si configuration [13]. After acid cleaning, the bands located at 470, 810 and 1090 cm is ascribed to Si-O stretching vibration of Si-OH groups [26], which is noticeable in the "acid-cleaned" curve and possible partially masked by the broad band around 1090 cm -1 in the "original" curve.…”
Section: Resultsmentioning
confidence: 94%
“…These defects lower the conduction band of the material to enable spontaneous emission of blue light (400-450 nm) under excitation by ultraviolet light of a higher energy, a process known as photoluminescence. Through controlled cell cultivation, the level of detail in the diatom frustule nanostructure can be increased, which in turn increases the defect density and the intensity of the blue photoluminescence emission [2].…”
Section: Commentarymentioning
confidence: 99%